Dataset of taxonomic identification from surface water in the coastal area of Peninsular Malaysia - Khairul Anuar, Ayu Nabila; Muhammad Zamri, Nur Khayyirah; Mohd Yuzaidey, Muhammad Abid; Su Nyun Pau, Suriyanti; Mustaffa, Nur Ili Hamizah (Elsevier Inc., 2024)
This article describes the abundance of phytoplankton community structures in Port Dickson and Pulau Tinggi during the Southwest and Northeast Monsoons and includes data from 48 selected sampling sites collected between July and December 2023. The seawater samples from 1-meter depth were obtained by using a Niskin water sampler, concentrated in a 50 ml centrifuge tube and immediately preserved with Lugol’s iodine solution. The data include phytoplankton density (cell L−1), the total density of phytoplankton in each station, and the total number of genera obtained in every station. Additional data are presented, including chlorophyll-a concentration, as a proxy for biomass and photosynthetic active radiation. This article presents data on 30 genera, including unidentified genera, as well as the percentage of the main community group.